Contributions of Sensory Coding and Attentional Control to Individual Differences in Performance in Spatial Auditory Selective Attention Tasks - Dai, Lengshi; Shinn-Cunningham, Barbara G. (Frontiers in Human Neuroscience, 2016)
Listeners with normal hearing thresholds differ in their ability to steer attention to whatever sound source is important. This ability depends on top-down executive control, which modulates the sensory representation of sound in cortex. Yet, this sensory representation also depends on the coding fidelity of the peripheral auditory system. Both of these factors may thus contribute to the individual differences in performance. We designed a selective auditory attention paradigm in which we could simultaneously measure envelope following responses (EFRs, reflecting peripheral coding), onset event-related potentials from the scalp (ERPs, reflecting cortical responses to sound), and behavioral scores. We performed two experiments that varied stimulus conditions to alter the degree to which performance might be limited due to fine stimulus details vs. due to control of attentional focus. Consistent with past work, in both experiments we find that attention strongly modulates cortical ERPs. Importantly, in Experiment I, where coding fidelity limits the task, individual behavioral performance correlates with subcortical coding strength (derived by computing how the EFR is degraded for fully masked tones compared to partially masked tones); however, in this experiment, the effects of attention on cortical ERPs were unrelated to individual subject performance. In contrast, in Experiment II, where sensory cues for segregation are robust (and thus less of a limiting factor on task performance), inter-subject behavioral differences correlate with subcortical coding strength. In addition, after factoring out the influence of subcortical coding strength, behavioral differences are also correlated with the strength of attentional modulation of ERPs. These results support the hypothesis that behavioral abilities amongst listeners with normal hearing thresholds can arise due to both subcortical coding differences and differences in attentional control, depending on stimulus characteristics and task demands.